STUDY OF THE RELATIONSHIP BETWEEN THE EXISTENCE OF CIPALI TOLL ROAD AND THE AMOUNT OF ECONOMIC ACTIVITY IN KABUPATEN CIREBON (CASE STUDY: EXIT TOLL CIWARINGIN, PLUMBON, TALUN, DAN ASTANAJAPURA SUB-DISTRICT) - Izhar, Ryansyah
The Cipali Toll Road Infrastructure (Cikopo - Palimanan) was inaugurated in 2015 precisely on June 13, 2015. The Cipali Toll Road is believed to be able to grow economic activities and can also cause negative impacts that will be felt by the community around the toll road especially in the area near the door toll (exit toll). Based on data from Bank Indonesia in 2015 the economy in Cirebon Regency increased due to the existence of the Cipali toll road. This research aims to find out the relationship between the existence of Toll Roads to increase economic activities to find out whether the factors or variables that cause an increase in economic activity in Cirebon Regency. To answer the objectives of this study there are three objectives to be achieved in this study, (1) What are the factors that influence the increase in economic activities in the Cirebon region. (2) What is the relationship between these factors to increase economic activity in the Cirebon region? 3) How big is the contribution of these factors in increasing economic activity in the Cirebon region. The method used in this study is the Hotspot Analysis method where this method is used to show the concentration of the location of economic activity and the Geographically Weighted Regression (GWR) method to see the relationship of factors believed to increase economic activity in the area around the toll gates. Based on the results of the analysis of the hotspots that have been conducted, the results show that the location of economic activities in Cirebon Regency tends to be concentrated in the area around the toll booth. The results of the GWR analysis in which there is an OLS (Ordinary Least Square) analysis process show that the causes of concentrations of economic activity in the area around toll gates are influenced by several factors, 1) Population, 2) Score of exit toll access, 3) Score of hub access, 4) Number of facilities, 5) Number of buildings, 6) Number of population with productive age. In addition, this study also found that the results of GWR calculations are better in OLS